2022
DOI: 10.3390/nu14173574
|View full text |Cite
|
Sign up to set email alerts
|

Crossbred Sows Fed a Western Diet during Pre-Gestation, Gestation, Lactation, and Post-Lactation Periods Develop Signs of Lean Metabolic Syndrome That Are Partially Attenuated by Spirulina Supplementation

Abstract: Excessive dietary intake of fats and sugars (“Western diet”, WD) is one of the leading causes of obesity. The consumption of the microalga Arthrospira platensis (spirulina, Sp) is increasing due to its presumed health benefits. Both WD and Sp are also consumed by pregnant and breastfeeding women. This study investigated if gestating and lactating domestic pigs are an appropriate model for WD-induced metabolic disturbances similar to those observed in humans and if Sp supplementation may attenuate any of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Based on these nutritional benefits, spirulina is now used as a food supplement for both humans and livestock. Spirulina can be used as an amino acid supplement in poultry and piglet diets and is effective in relieving sows from nutritional metabolism disorders due to gestation (7)(8)(9). A previous study showed that it was beneficial to lamb growth when they were fed 20% spirulina supplementation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these nutritional benefits, spirulina is now used as a food supplement for both humans and livestock. Spirulina can be used as an amino acid supplement in poultry and piglet diets and is effective in relieving sows from nutritional metabolism disorders due to gestation (7)(8)(9). A previous study showed that it was beneficial to lamb growth when they were fed 20% spirulina supplementation (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two articles specifically delve into lipid metabolism in unique populations. The study by R. Lugarà et al investigates the impact of a Western diet on gestating and lactating sows, revealing signs of lean metabolic syndrome characterized by disrupted cholesterol levels, decreased IGF1 levels, and indications of hepatic damage [ 6 ]. Spirulina supplementation in this context partially mitigates these effects, hinting at its potential to counteract some of the negative outcomes associated with a Western diet.…”
Section: Obesity and Metabolic Disordersmentioning
confidence: 99%
“…Depended on nutritional advantage, SP is now considered as a food addictive for human and animals. Spirulina could be deemed as an amino acid addictive in piglet and poultry diets and it plays a vital role in relieving pigs from nutritional metabolism disturbance due to pregnancy (Lugarà et al, 2022).…”
Section: Introductionmentioning
confidence: 99%